THE CARTOGRAPHY AS TEXT AND TOOL OF WORLD MODALIZATION - Ferrús Antón, Beatriz (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2015)
The American work of Baroness Wilson it’s a good example to study how in the XIX century the “battle” for the world models is lived, as a result of this meeting among the old representations of the American that arise from the chronicles and those new ones produced by the criolla ideology.This article works the notions of world model and modeling of the critic as a sabotage (Asensi) illustrated over this textual corpus. The way of the women is represented in this context it’s also decisive.